Crowdsourcing Mobile Web Applications - Challiol, Cecilia (2013)
Building Mobile Web or Hypermedia Applications is usually difficult since there is a myriad of issues to take into account. Moreover adding support for personalized or context-aware behaviors goes far beyond the possibilities of many kinds of organizations that intend to build this kind of software (museums, city halls, etc). In this article we present a novel approach to delegate part of the effort in building mobile Web software to developers outside those organizations or even to final users. We show that this approach is feasible, light and practical and present a set of experiments we developed to verify our claims.